PENGARUH REFORMASI STRUKTUR BIROKRASI TERHADAP KINERJA ORGANISASI PADA SEKRETARIAT DAERAH KOTA MANADO - UMASUGI, RAHMAT; Kiyai, Burhanuddin; Palar, Novie (Sam Ratulangi University, 2017)
Abstract:This research aims to know the influence of the reform of the Organization's performance against bureaucratic structures in the Secretariat of the regional city of manado. This research using quantitative methods. The respondents in this study amounted to 99 employees at the Secretariat of the regional city of manado. Data collection instruments and techniques used are questionnaire and assisted with interviews and observation. Analytical techniques used for hypothesis testing is the analysis of the correlation of product moment and linear regression with aided by data processing computer program SPSS version 20. The results of data analysis in this research indicate: (1) strong linkages among variables reform bureaucratic structure with organizational performance the Secretariat of Manado City area namely the correlation coefficient was obtained (r) of 0.611 and the coefficient of determination (r2), obtained of 0.373. (2) this can be explained further that the influence of the reform of the Organization's performance against the bureaucratic structure of the Secretariat of the regional city of Manado of 37.3%, while the rest of 62.7% determined by other factors not examined in this study. (3) the results showed that the average performance of organization reform post-war bureaucratic structure acquired for 45.82 or in pengkuran of ideal scale 0.9164 or 91.64%, while the performance of the organization prior to the implementation of the reform of the structure of the bureaucracy, only of 39.96 or in Hiiumaa ideal measurements acquired for 0.7992 or 79.92%, making it a very real differences occur, i.e. around 11.72%.Keywords: reform of the bureaucratic structure, organizational performance, Setda